Genetic variation, phylogenetics and fruit quality characteristics of Physalis minima L. in Peninsular Malaysia - Usaizan, Norhanizan (2017)
Physalis is a member of the Solanaceae family and it is abundantly found growing as weeds in Malaysia. This plant reported to have various antioxidants, antimicrobials and anticancer compounds such as physalin B and F which have great potential for tumors treatment. However, due to its classification as weed, little attention is given. There is a lack of information on genetic variation and phylogenetic relationship including genetics distance to the other member of Solanaceae family. A germplasm collection consisted of 130 samples representing 19 accessions from 11 states of Peninsular Malaysia was established. Physalis minima was found growing under various environmental conditions including at farm, plantation area (especially of oil palm (Elaeis guineensis)), thus proving its high adaptability to a wide variety of ecological niches in Peninsular Malaysia.